বাংলা পাণ্ডুলিপি পাঠসমীক্ষা - মিয়া, মুহাম্মদ শাহজাহান (ঢাকা : বাংলা একাডেমী, 1984)
Study of Bengali manuscripts preserved in the University of Dacca Library.
Includes Bibliography: (p. [226]-230) and indexes.
In Bengali.
Keywords: University of Dhaka. -- Library -- Catalogs; Manuscripts, Bengali -- Catalogs; Manuscripts, Sanskrit -- Bangladesh -- Dhaka -- Catalogs